“COVID-19 – Current Status and Trends: A Comprehensive Review - Cinosh Mathew1 , Jayesh Rawal2 , Nishant Saxena3 , Ashish Sharma3 , Rahul Jain3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
The current global pandemic of COVID-19 is caused by a virus of corona family named SARS-CoV-2.Cardiovascular manifestations of COVID-19 are varied and complex and include myocarditis, acutecoronary syndrome, heart failure, pericarditis and pericardial effusion. Those with cardiac comorbidites areat higher risk of severe infection and death. SARS-CoV-2 may infiltrate and injury the heart directly or maycause Myocardial infarction, LV dysfunction secondary to myocarditis, congestive cardiac failure, rhythmabnormalities and pulmonary and other vascular embolisms. The medications used to treat COVID-19 mayalso have serious cardiac side effects. A through understanding of the cardiac involvement of COVID-19and its varied presentation is needed for management of COVID-19 infection and its complications.